A Web Application for Condominium Complaint Management - สุวิสิษฐ์, ปพนวิทย์; วิไลชัยกุล, อรรถพล; พ่วงกำเหนิด, สุพจน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to develop a web-based application for managing complaint and maintenance requests within condominium projects and to evaluate its system performance and user satisfaction. The System Development Life Cycle (SDLC) was adopted as the development framework, consisting of planning, analysis, design, development, testing, and implementation phases to ensure a systematic and reliable system development process. The sample group consisted of 30 users selected through purposive sampling, including 5 administrators, 10 technicians, and 15 residents. The research instruments included the developed web application and a user satisfaction questionnaire based on a 5-point Likert scale. Data were analyzed using descriptive statistics, including percentage, mean, and standard deviation. The results indicated that the developed system functioned correctly according to the specified requirements. It effectively supported core functionalities such as complaint submission, user management, and job status tracking. The overall user satisfaction was at a high level (Mean = 4.35, S.D. = 0.56), demonstrating that the system is appropriate for real-world implementation. In conclusion, the developed web application enhances the efficiency of complaint and maintenance management within condominium projects by reducing process redundancy, improving communication, and enabling real-time status tracking. Furthermore, the system can be extended and adapted for broader applications in other real estate management contexts.